117k views
8 votes
Place each function below in the appropriate cell to show the transformation from

Place each function below in the appropriate cell to show the transformation from-example-1

1 Answer

2 votes

Answer:

See below ↓↓↓↓

Explanation:

Top left box

f(x) = 2x² + 4

g(x) = 2f(x) - 3

  • g(x) = 2(2x² + 4) - 3
  • g(x) = 4x² + 8 - 3
  • g(x) = 4x² + 5

Top right box

f(x) = 2x² + 4

g(x) = 2f(x) + 3

  • g(x) = 2(2x² + 4) + 3
  • g(x) = 4x² + 8 + 3
  • g(x) = 4x² + 11

Bottom left box

f(x) = 2x² - 4

g(x) = 2f(x) - 3

  • g(x) = 2(2x² - 4) - 3
  • g(x) = 4x² - 8 - 3
  • g(x) = 4x² - 11

Bottom right box

f(x) = 2x² - 4

g(x) = 2f(x) +3

  • g(x) = 2(2x² - 4) + 3
  • g(x) = 4x² - 8 + 3
  • g(x) = 4x² - 5
User Ryandenki
by
4.5k points